2020
DOI: 10.1080/1828051x.2020.1853620
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary chromium-yeast level on growth performance, blood metabolites, meat traits and muscle fatty acids profile, and microminerals content in liver and bone of lambs

Abstract: Rodríguez-Gaxiola (2020) Effects of dietary chromiumyeast level on growth performance, blood metabolites, meat traits and muscle fatty acids profile,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 58 publications
(69 reference statements)
2
0
0
Order By: Relevance
“…On the other hand, burger of yeast group had the lowest index of atherogenicity (IA) which is healthier for human consumption. These results are constant with Morenocamarena et al [16] result, where they found that dietary supplement with different levels of chromium-yeast decreased the palmitic (C16:0) and stearic (C18:0), while palmitoleic (C16:1n-7), vaccenic (C18:1n-7), linoleic (C18:2n-6) and arachidic (C20:4) fatty acids increased in lamb meat. Addition of yeast in sheep diets significantly decreased (p<0.05) the content of saturated, increased the content of monounsaturated and total of unsaturated fatty acids.…”
Section: Fatty Acid Profilesupporting
confidence: 85%
See 1 more Smart Citation
“…On the other hand, burger of yeast group had the lowest index of atherogenicity (IA) which is healthier for human consumption. These results are constant with Morenocamarena et al [16] result, where they found that dietary supplement with different levels of chromium-yeast decreased the palmitic (C16:0) and stearic (C18:0), while palmitoleic (C16:1n-7), vaccenic (C18:1n-7), linoleic (C18:2n-6) and arachidic (C20:4) fatty acids increased in lamb meat. Addition of yeast in sheep diets significantly decreased (p<0.05) the content of saturated, increased the content of monounsaturated and total of unsaturated fatty acids.…”
Section: Fatty Acid Profilesupporting
confidence: 85%
“…Regards to feeding on medicinal plants, the results of the current study contradict the findings of Redoy et al [20] they found that sheep meat of herbal-supplemented feeding groups had lower saturated fatty acids and higher unsaturated fatty acids content compared with the control diet group. Data of atherogenic index of sheep burger came in accordance with the results of [16] they found that significant decrease was found in the index of atherogenicity in sheep Longissimus dorsi as the level of yeast in the diet increased. Similar results were found by [17].…”
Section: Fatty Acid Profilesupporting
confidence: 80%